Modeling glacier-surface albedo across Svalbard for the 1979-2015 period: The HiRSvaC500-α data set - Möller, Marco; Möller, Rebecca (RWTH Aachen University, 2017)
Journal of advances in modeling earth systems : JAMES 9(1), 404-422 (2017). doi:10.1002/2016MS000752 : Published by AGU, Fort Collins, Colo.